2015
DOI: 10.1016/j.plaphy.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cell size and number and in rhizodermal development contribute to root tip swelling of Hyoscyamus albus roots subjected to iron deficiency

Abstract: Root tip swelling is a common phenomenon observed when plant roots are subjected to Fe deficiency. We analysed whether an increase in cell number or an enlargement of cell width was involved in this phenomenon. Root tips of Hyoscyamus albus cultured with or without Fe were stained with fluorescent SYTO14 and analysed by confocal laser-scanning microscopy. Time-course and position-based examination revealed that the inhibition of longitudinal cell elongation and acceleration of transverse cell enlargement under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…At the physiological level, there was an increased expression of ferritin in the leaves and of an iron-regulated transporter (irt1) in the roots (Boamponsem et al, 2017). Kawahara and Kitamura (2015) reported that the swelling of root tips in Hyoscyamus albus L. (Solanaceae) subjected to Fe depletion was related to changes in both cell size and number, and to the development of root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…At the physiological level, there was an increased expression of ferritin in the leaves and of an iron-regulated transporter (irt1) in the roots (Boamponsem et al, 2017). Kawahara and Kitamura (2015) reported that the swelling of root tips in Hyoscyamus albus L. (Solanaceae) subjected to Fe depletion was related to changes in both cell size and number, and to the development of root hairs.…”
Section: Discussionmentioning
confidence: 99%